2011
DOI: 10.1002/cphc.201100105
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐State‐Mediated Charge‐Transfer Dynamics in CdTe/CdSe Core–Shell Quantum Dots

Abstract: Herein, we report the synthesis of aqueous CdTe/CdSe type-II core-shell quantum dots (QDs) in which 3-mercaptopropionic acid is used as the capping agent. The CdTe QDs and CdTe/CdSe core-shell QDs are characterized by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HR-TEM), steady-state absorption, and emission spectroscopy. A red shift in the steady-state absorption and emission bands is observed with increasing CdSe shell thickness over CdTe QDs. The XRD pattern indicates that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 62 publications
2
44
0
1
Order By: Relevance
“…6 Secondly, they are the only Type II CQD yet demonstrated to emit at wavelengths less than 500 nm, thus enabling gain in the blue part of the spectrum. [11][12][13][14][15][16][17][18][19][20][21] Lastly, they are also unique amongst Type II CQDs in being free of toxic elements such as Cd and Pb, the use of which is heavily restricted by legislation. 22 This study has shown, as for CdSe and PbSe CQDs, that the surface-trapping of photogenerated charges can play an important role in the sub-nanosecond exciton dynamics of ZnTe-ZnSe CQDs.…”
Section: Comparison To Other Cqdsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Secondly, they are the only Type II CQD yet demonstrated to emit at wavelengths less than 500 nm, thus enabling gain in the blue part of the spectrum. [11][12][13][14][15][16][17][18][19][20][21] Lastly, they are also unique amongst Type II CQDs in being free of toxic elements such as Cd and Pb, the use of which is heavily restricted by legislation. 22 This study has shown, as for CdSe and PbSe CQDs, that the surface-trapping of photogenerated charges can play an important role in the sub-nanosecond exciton dynamics of ZnTe-ZnSe CQDs.…”
Section: Comparison To Other Cqdsmentioning
confidence: 99%
“…[8][9][10] To date ultrafast exciton dynamics have been studied in Type II CQDs utilising CdE (E = Se, S or Te) for either the core or shell material, or both. These core-shell structures have included CdS-ZnSe, 6 ZnTe-CdSe, 11 CdTe-CdSe, [12][13][14][15][16] ZnSe-CdS, 17 CdTe-CdS, 18 CdSe-ZnTe, 19 CdTe-ZnTe 20 and CdSe-ZnS. 21 However, the use of cadmium is heavily regulated because of its toxicity by, for instance, the Restriction of Hazardous Substances Directive of the European Union; 22 other jurisdictions have similar legislation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could probably be explained by the more intense electron−hole feature from the dangling bond of BP as a result of the aggregation of BP on the CdS surface. 37 Comparison between the normalized transient absorption dynamics for the bleach recovery at 737 nm is presented in Figure 4b for the different BP-mediated materials. In bare BP QDs, as summarized in Table 1, two fast decay components were observed, which could be ascribed to the exciton recovery to the ground state (1.7 ps) and residual cooling of the trapped electrons in superficial defect states of BP (10 ps), respectively.…”
mentioning
confidence: 99%
“…点,[18][19][20] 近年来也有关于 ZnSe/ZnS 量子点的报道,[21][22][23] 但目前对 Cu 掺杂的 ZnSe 量子点表面修饰的研究报 道 较 少, 主 要 是 以 TAA 和 Na2S 24,25 为 硫 源 制 得 的 ZnSe:Cu/ZnS 量子点为主,…”
unclassified